(untitled) (Archives of Clinical Psychiatry, 2003)
This research analyzed the psychometric property of test-retest reliability of the Brazilian version of the Independent Living Skills Survey scale (ILSS-BR), developed to provide global assessments of functional living skills of chronically mentally ill individuals. Previous research have demonstrated that the ILSS-BR had good psychometric properties of reliability and validity, in terms of the internal consistency of its sub-scales, construct validity of the scale and discriminant validity, but have not analyzed its temporal stability. The results of the present research showed significant correlation coefficients between the test and the retest scores of the ILSS-BR, for each of its sub-scales and for the global score. This result demonstrated that the ILSS-BR has temporal stability and is a reliable scale to be used in the planning and evaluation of psychosocial rehabilitation program for psychiatric patients, in brazilian context.